Ejermærker i Danmarks Kunstbiblioteks ældre samling 1754 til 1810 - Kragelund, Patrick (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Patrick Kragelund: Owners Marks in Early Aquisitions of the Danish National Art Library   The article provides a historical survey of owners’ marks, of exlibrises and superexlibrises in the early section (acquisitions 1754–1810) of the holdings of the Danish National Art Library. From the early part of this period a few royal gifts have been preserved, but the largest part of the material of relevance entered the library with the acquisition of the painter Nicolai Abildgaard’s books in 1810. It includes items with the superexlibris of King Charles XI of Sweden and Duke Friedrich III of Slesvig-Holstein-Gottorp (the latter a gift from Athanasius Kircher) and books from Danish 17th century private libraries, among which the author and translator Birgitta Thott. In the Royal Academy context, books once belonging to three of the early Dutch and German immigrant artists active in early 18th century Denmark such as Johann Coning, Otto de Willarts and Marcus Tuscher are of particular interest.